Calorimetric Determination of Heat Capacity, Entropy and Enthalpy of Mixed Oxides in the System CaO–SrO–Bi2O3–Nb2O5–Ta2O5 - Leitner, Jindřich; Sedmidubský, David; Růžička, Květoslav; Svoboda, Pavel (IntechOpen, 2013)
None